People with epilepsy receive more statins than the general population but have no higher cardiovascular risk: results from a cross‐sectional study. (21st December 2016) - Vivanco‐Hidalgo, R. M.; Elosua, R.; Gómez González, A.; Moreira, A.; Díez, L.; Grau, M.; Degano, I. R.; Roquer, J.
Abstract : Background and purpose: Epilepsy has been associated with cardiovascular comorbidity. Risk prediction equations are the standard tools in primary prevention of cardiovascular disease. Our aim was to compare the prevalence of cardiovascular risk factors (CVRFs), cardiovascular risk and statin use in people with epilepsy (PWE) and the general population. Methods: The CVRFs and cardiovascular risk score were compared between 815 PWE from an outpatient register and 5336 participants from a general population cohort. Results: People with epilepsy had less hypertension (43.3% vs. 50.4%), less diabetes (15.8% vs. 19.2%), more dyslipidemia (40.2% vs. 34.6%) and lower cardiovascular risk than the general population ( P < 0.01). No etiology was associated with a worse CVRF profile or higher cardiovascular risk. Patients taking enzyme‐inducing antiepileptic drugs (EIAEDs) had more dyslipidemia than the general population (41.6% vs. 34.6%) but similar cardiovascular risk. Independently of risk or CVRFs, PWE had 60% more probability of receiving statins than the general population. Conclusions: People with epilepsy had more dyslipidemia, related to EIAEDs, and lower cardiovascular risk but still took more statins than the general population. Physicians should use clinical judgement to decide on further treatment of CVRFs in PWE who are below the recommended risk threshold for treatment and should consider lipid abnormalities a potential side‐effect of EIAEDs. Other therapy options may need to be evaluated before starting lipid‐lowering treatment.